The implementation of smart city concepts in the area of Greater Kuching Sarawak / Gerraint Gillan Ahi and Ts. Dr. Nor Hanisah Mohd Hashim - Ahi, Gerraint Gillan; Mohd Hashim, Nor Hanisah (College of Built Environment, 2023)
Smart city implementation in Greater Kuching, sARAWAK, is the subject of this study.